2003
DOI: 10.1073/pnas.1332697100
|View full text |Cite
|
Sign up to set email alerts
|

An unusual internal ribosomal entry site of inverted symmetry directs expression of a potato leafroll polerovirus replication-associated protein

Abstract: Potato leafroll polerovirus (PLRV) genomic RNA acts as a polycistronic mRNA for the production of proteins P0, P1, and P2 translated from the 5 -proximal half of the genome. Within the P1 coding region we identified a 5-kDa replication-associated protein 1 (Rap1) essential for viral multiplication. An internal ribosome entry site (IRES) with unusual structure and location was identified that regulates Rap1 translation. Core structural elements for internal ribosome entry include a conserved AUG codon and a dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 63 publications
1
54
0
4
Order By: Relevance
“…Therefore, BLucB is eIF4F, and thus, BTE dependent. Finally, observations that some plant and mammalian virus IRESes can stimulate translation of upstream AUGs (Jaag et al 2003;Herbreteau et al 2005;Nicholson et al 2006;Junemann et al 2007) may be explained by mechanisms similar to that shown in Figure 7.…”
Section: A Model For Bte-mediated Cap-independent Translationmentioning
confidence: 80%
“…Therefore, BLucB is eIF4F, and thus, BTE dependent. Finally, observations that some plant and mammalian virus IRESes can stimulate translation of upstream AUGs (Jaag et al 2003;Herbreteau et al 2005;Nicholson et al 2006;Junemann et al 2007) may be explained by mechanisms similar to that shown in Figure 7.…”
Section: A Model For Bte-mediated Cap-independent Translationmentioning
confidence: 80%
“…In bicistronic systems, detection of the product encoded by the second cistron is evidence that the first cistron is also being expressed. This approach has been used successfully in gene therapy research in animal systems, and IRESes from different viruses have been tested and shown to function in plant systems (Urwin et al, 2000(Urwin et al, & 2002Dorokhov et al, 2002;Jaag et al, 2003;Bouabe et al, 2008).…”
Section: Expression Of Multiple Genesmentioning
confidence: 99%
“…14), los tres genes más próximos al extremo 5' se traducen a partir del gRNA, mientras que el resto de ORFs localizadas aguas abajo, lo hacen a partir de sgRNAs (Tacke et al, 1990; 46 Introducción General Ashoub et al, 1998). Hasta el momento no se ha identificado ningún elemento en la 5' UTR capaz de mediar la traducción por un mecanismo independiente de cap; sin embargo se ha descrito una secuencia que permite la traducción de una proteína de 5 kDa, denominada Rap1, codificada por un gen imbricado dentro de la ORF2 (Jaag et al, 2003) (Fig. 14).…”
Section: Introducción Generalunclassified
“…La función específica de Rap1 se desconoce, pero es indispensable para la replicación viral. La secuencia, que actúa como IRES, se localiza alrededor de 1500 nt aguas abajo del extremo 5' del gRNA (Jaag et al, 2003), y se caracteriza por un motivo rico en polipurinas, GGAGAGAGAGG, situado 22 nt aguas abajo del codón de inicio del gen de la Rap1. Este motivo, junto con los primeros 22 nt del gen de la Rap1, es suficiente para mediar la traducción por un mecanismo independiente de cap in vitro, pero no in vivo (Jaag et al, 2003).…”
unclassified
See 1 more Smart Citation